Preferences, Needs, and Demand Analysis of Health Facilities Development - Gusniawan, Rino Indira; Kumalasari, Berti; Azizah, Yasmin (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Health is one aspect that determines human living standards. Health is needed to support all life activities, and health facilities are required to provide a healthy community. This study aimed to identify and analyze the relationship between preferences, needs, and demands for developing health facilities in Bogor City. Data were collected in May 2023. A total of 201 research respondents participated in the study. The relationship test showed that the mother's occupation and preference had a significant positive relationship with the level of interest, and the mother's employment and level of interest had a significant positive relationship with the level of need. Monthly family expenditure had a significant negative association with the level of need, mother’s age had a significant negative relationship with the demand for the construction of health facilities, and family size and grade of importance had a significant positive relationship with the demand for health facility development.